2009
DOI: 10.1016/j.resp.2009.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of respiratory activity after C2 hemisection (C2HS): Involvement of adenosinergic mechanisms

Abstract: Consequences of spinal cord injury (SCI) depend on the level and extent of injury. Cervical SCI often results in a compromised respiratory system. Primary treatment of SCI patients with respiratory insufficiency continues to be with mechanical ventilatory support. In an animal model of SCI, an upper cervical spinal cord hemisection paralyzes the hemidiaphragm ipsilateral to the side of injury. However, a latent respiratory motor pathway can be activated to restore respiratory function after injury. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…1,2 These pathways monosynaptically 23,24 or polysynaptically (via spinal interneurons 6,22,25,26 ) innervate PhMNs ipsilateral to injury, restoring inspiratory drive and phrenic motor output. Several studies have also shown that this plasticity is regulated by serotonin, 27,28 adenosine, 29 and glutamate. 28,30,31 Although acute activation of the CPP supports the presence of an existing latent pathway, previous studies have also revealed that ongoing neuroanatomical reorganization and recruitment of polysynaptic pathways associated with the sCPP likely contribute to further changes within crossed-phrenic pathways and long-term recovery.…”
Section: Discussionmentioning
confidence: 96%
“…1,2 These pathways monosynaptically 23,24 or polysynaptically (via spinal interneurons 6,22,25,26 ) innervate PhMNs ipsilateral to injury, restoring inspiratory drive and phrenic motor output. Several studies have also shown that this plasticity is regulated by serotonin, 27,28 adenosine, 29 and glutamate. 28,30,31 Although acute activation of the CPP supports the presence of an existing latent pathway, previous studies have also revealed that ongoing neuroanatomical reorganization and recruitment of polysynaptic pathways associated with the sCPP likely contribute to further changes within crossed-phrenic pathways and long-term recovery.…”
Section: Discussionmentioning
confidence: 96%
“…This model is currently used by several laboratories around the world (for reviews: [4][5][6][7][8][9][10][11][12][13] ). However, slight differences in the surgical procedure can be observed among the different investigators to generate this particular cervical injury murine model.…”
Section: Introductionmentioning
confidence: 99%
“…In non-toxic concentrations, the methylxanthines caffeine and theophylline are non-selective antagonists of the adenosine receptors (Fredholm, 2007, Fredholm, et al, 1999). Clinically, apnea of prematurity can be treated effectively with caffeine (Schmidt, et al, 2007); likewise, inhibition of adenosine receptors with theophylline was shown to restore spontaneous respiration after spinal cord injury (Nantwi, 2009). Thus, methylxanthines can be used experimentally and therapeutically to influence adenosine-based modulation of respiratory function.…”
Section: Introductionmentioning
confidence: 99%